Tinjauan Yuridis Putusan Constitutional Review Mahkamah Konstitusi Tentang Hak Mantan Narapidana Untuk Menjadi Pejabat Publik Yang Dipilih - Nanang Nur Wahyudi; Nynda Fatmawati Octarina (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
Political rights are protected by law, both internationally and nationally. Internationally, political rights are regulated by the Universal Declaration of Human Rights (UDHR) and the International Covenant on Civil and Political Rights (ICCPR). Political rights are also protected by our constitution and several other laws and regulations, especially Law No. 39 of 1999 concerning Human Rights. There is a provision which is a requirement to run for election which clearly limits and even negates a person's right to participate in exercising their human rights. This is clearly a violation of a person's human rights, which in this case the political rights of an ex-convict, especially in cases of corruption. If we look at the provisions of the 1945 Constitution, an ex-convict is also a citizen who has the same political rights as other citizens. The right to judicial review of regulations that are contrary to the 1945 Constitution, the authority of the right to examine lies with the Constitutional Court (MK). The Constitutional Court's decision provides legal certainty that a former convict in a corruption case is still allowed to run for regional head elections because ex-convicts still have political rights as citizens. To be able to run for regional head elections, ex-convicts after passing through a period of 5 (five) years have finished serving their sentence and have returned to community life as other people's lives. Respect the political rights of ex-convicts of corruption cases as an acknowledgment of human rights in the Republic of Indonesia which are constitutional rights regulated in the 1945 Constitution.Keywords: Prisoners, Judicial Review, Rights, Constitutional Court Decisions Abstrak:Hak Politik dilindungi hukum, baik secara internasional maupun nsional. secara internasional, hak politik diatur Universal Declaration of Human Rights (UDHR) dan International Covenant on Civil and Political Rights (ICCPR). Hak politik juga dilindungi konsitusi kita dan beberapa peraturan Perundang-Undangan lainnya, serutama Undang-Undang no 39 tahun 1999 tentang Hak Asasi Manusia. Adanya ketentuan yang merupakan syarat untuk mencalonkan diri pada pemilihan yang jelas membatasi bahkan meniadakan hak seseorang untuk ikut serta dalam menggunakan hak azasinya. Hal ini jelas merupakan pelanggaran terhadap hak azasi seseorang, yang dalam hal ini hak politik yang dimiliki oleh seorang mantan narapidana khususnya pada kasus korupsi. Apabila kita mencermati ketentuan UUD 1945, maka seorang mantan narapidana juga sebagai warga negara yang memiliki hak politik yang sama dengan warga negara lainnya. Hak Uji materiel terhadap peraturan yang bertentangan dengan Undang-Undang Dasar 1945, maka kewenangan hak menguji ada pada Mahkamah Konstitusi (MK). Putusan Mahkamah Konstitusi memberi kepastian hukum bahwa seorang mantan Narapidana kasus korupsi masih diperbolehkan untuk mencalonkan diri pada pemilihan kepala daerah karena mantan narapidana masih memiliki hak politik sebagai warga negara. Untuk dapat mencalonkan diri pada pemilihan kepala daerah, maka mantan narapidana setelah melewati masa 5 (lima) tahun selesai menjalani masa hukuman dan telah kembali kepada kehidupan masyarakat sebagaimana kehidupan masyarakat lainnya. Menghormati hak politik mantan narapidana kasus korupsi sebagai pengakuan terhadap hak azasi manusia dalam negara Republik Indonesia yang merupakan hak konstitusional yang diatur dalam UUD Tahun 1945.Kata Kunci: Narapidana, Judisial Review, Hak, Putusan Mahkamah Konstitusi